Recognising excellence in university mathematics teaching and learning - Lonsdale, Heather (2018)
This article is the first in a series, organised by the AustMS Standing Committee on Mathematics Education, and seeks to recognise contributions to teaching and learning. In particular this article will highlight the work of three mathematicians who were recipients of 2017 AAUT Citations for Outstanding Contributions to Student Learning: Poh Hillock, Deborah Jackson, and Stephen Woodcock.